Luxembourg : Financial Sector Assessment Program: Technical Note-Selected Issues in Banking Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This Technical Note examines aspects of the banking supervision regime in Luxembourg. Significant progress has been made in relation to the recommendations made in the 2011 Financial Sector Assessment Program. The Finance Ministry is no longer responsible for the granting or revocation of banking licenses, the Commission for the Supervision of the Financial Sector (CSSF) is no longer charged with promoting industry, resources have increased substantially, and there has been a significant increase in the implementation of sanctioning powers. There still exists potential for government or industry interference in the operational independence of the CSSF. The frequency of on-site inspections of Luxembourg subsidiaries of significant institutions is also on the low side.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet